A companion to Lyndon B. Johnson - Lerner, Mitchell B., 1968- (Chichester, UK : Wiley-Blackwell, 2012)
This companion offers an overview of Lyndon B. Johnson's life, presidency, and legacy, as well as a detailed look at the central arguments and scholarly debates from his term in office. Explores the legacy of Johnson and the historical significance of his years as president. Covers the full range of topics, from the social and civil rights reforms of the Great Society to the increased American involvement in Vietnam. Incorporates the dramatic new evidence that has come to light through the release of around 8,000 phone conversations and meetings that Johnson secretly recorded as President.
The changing South / Jeff Woods -- LBJ in the House and Senate / Donald A. Ritchie -- The vice presidency / Marc J. Selverstone -- Lady Bird Johnson / Lisa M. Burns -- Management and vision / Sean J. Savage -- The war on poverty / Edward R. Schmitt -- African-American civil rights / Kent B. Germany -- Mexican Americans / Lorena Oropeza -- Women's issues / Susan M. Hartmann -- Health care / Larry DeWitt and Edward D. Berkowitz -- Environmental policy / Martin V. Melosi -- American immigration policy / Donna R. Gabaccia and Maddalena Marinari -- LBJ and the Constitution / Robert David Johnson -- The urban crisis / David Steigerwald -- Education reform / Lawrence J. McAndrews -- Domestic insurgencies / Doug Rossinow -- LBJ and the conservative movement / Jeff Roche -- Decisions for war / Andrew Preston -- Fighting the Vietnam War / Robert D. Schulzinger -- The war at home / Mary Ann Wynkoop -- The war from the other side / Pierre Asselin -- Latin America / Alan McPherson -- Europe / Thomas Alan Schwartz -- LBJ and the Cold War / John Dumbrell -- The Middle East / Peter L. Hahn -- LBJ and the new global challenges / Mark Atwood Lawrence -- How great was the Great Society? / Sidney M. Milkis -- Lyndon B. Johnson and the world / Nicholas Evan Sarantakes -- The legacy of Lyndon B. Johnson / Andrew L. Johns.
Includes bibliographical references and index.
Print version record.
Keywords: Johnson, Lyndon B. -- 1908-1973.; Johnson, Lyndon B. -- 1908-1973 -- Political and social views; Johnson, Lyndon B., -- 1908-1973; Johnson, Lyndon B., -- 1908-1973 -- Political and social views; Johnson, Lyndon B. -- 1908-1973.; 1960-1980; Vietnam War, 1961-1975.; Presidents -- United States -- Biography; HISTORY -- United States -- 20th Century; Diplomatic relations; Political and social views; Politics and government; Presidents; Social conditions; United States -- Politics and government -- 1963-1969.; United States -- Social conditions -- 1960-1980.; United States -- Foreign relations -- 1963-1969.; United States; Electronic books; Biography; Electronic books